Grain yield and quality performances of different late-season rice cultivars in response to experimental warming in subtropical China - Yang, Taotao; Tan, Xueming; Huang, Shan; Pan, Xiaohua; Zeng, Yongjun; Zhang, Jun; Cheng, Shanmei; Zeng, Yanhua (Frontiers in Plant Science, 2023)
Introduction Climate warming has pronounced effects on rice production in China. However, late-seasons rice cultivars are diverse in double rice cropping systems, and the actual responses in grain yield and quality of different late-season rice cultivars to climate warming are still unclear. Methods A two-year field warming experiment was conducted by using free-air temperature increase facilities with three widely-planted late-season rice cultivars, including Taiyou398 (TY, short growth duration indica hybrid rice), Jiuxiangnian (JXN, long growth duration indica inbred rice), and Yongyou1538 (YY, long growth duration indica-japonica hybrid rice) in a double rice cropping system in subtropical China. Results Warming (1.9–2.0°C) had no significant effects on the grain yields of TY and JXN, but significantly decreased that of YY by 4.8% relative to ambient treatment due to a reduction of spikelet number. Compared to ambient treatment, the head rice yields of TY and YY did not change while that of JXN increased by 6.3% under warming conditions. Warming significantly increased the head rice rates of JXN and YY by 6.6% and 7.8%, and the chalky grain rates of TY, JXN, and YY by 79.1%, 21.6%, and 7.6%, respectively. Under warming conditions, the amylose content of JXN and YY decreased significantly by 7.5% and 8.8%, and the setback of three cultivars decreased significantly by an average of 41.5%. Conclusion Warming could improve the milling and eating qualities of long growth duration late-season rice (JXN and YY) and increase or maintain their head rice yield, even though decreased the grain yield of indica-japonica hybrid rice (YY). These results will provide a better understanding for the selection of suitable late-season rice cultivars under future climate warming conditions.